Perancangan Permainan Edukasi untuk Pendidikan Kebencanaan bagi Anak oleh Relawan Muhammadiyah Disaster Management Center Lampung: Educational Game Design for Disaster Education for Children by Muhammadiyah Disaster Management Center Lampung Volunteers - An Nur, Muhammad Hajid; Indrayati, Refita Ika; Rohman, Tefur Nur; Pustika, Reza (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Indonesia is classified as a country vulnerable to natural disasters, including tsunamis. The information about pre-disaster knowledge and tsunami preparedness needs to be passed on to the public, especially children. Earthquakes and tsunamis can happen at any time and hit anyone, including children, so it's important to conduct disaster education in schools. But in the event of a disaster, schools in the area must be vacant and replaced by volunteers of hatred. So hatred volunteers like Muhammadiyah Disaster Management Center are the right institutions to give educational games for hatred education. The activities of dedication to this community are carried out in three stages: 1) Design and production of toys and educational games; 2) Design trials for partners; and 3) Analysis of the results of the SUS (System Usability Scale) of partners. The results of this activity are toy design and education games that are well designed and accepted by MDMC partners Lampung and have SUS scores quite good with design 2 (Category B, 74.8) and design 3 (Category B, 71.1). However, design 1 still has a score below the average standard and requires improvement before it can be used in the field as one of the alternative educational media for tsunami prevention.